Hubungan Kesadaran Epistemologis Dengan Kemampuan Literasi Membaca Siswa Sekolah Dasar - Nainggolan, Guido; Sang Putri Zega, Ribka; Pratiwi, Cindy; Saragi, Daulat (Journal of Practice Learning and Educational Development, 2026)
This study aims to examine the effect of epistemological awareness-based learning interventions on the reading literacy skills of elementary school students. The background of this research is based on the low reading literacy of Indonesian students and the importance of the internal variable of epistemological beliefs in influencing how students understand texts. The research uses a quasi-experimental method with a nonequivalent control group pre-test/post-test design. The research subjects consisted of 60 fifth-grade students from PAB 27 Tanjung Mulia Private Elementary School in Medan City, who were divided into an experimental group and a control group. The research instruments include a reading literacy test based on the PISA framework and an epistemological awareness questionnaire that have been tested for validity and reliability. The treatment in the form of problem-based reading instruction with multiperspective texts was given to the experimental group for eight weeks, while the control group learned using conventional methods. The results of the ANCOVA analysis showed a significant difference in post-test reading literacy scores between the two groups, F(1,57)=18.74, p<0.001. The increase in the average reading literacy score in the experimental group was higher (16.70 points) compared to the control group (6.60 points). These findings affirm that interventions stimulating epistemological awareness effectively enhance students' reading literacy in depth. The implications of this research encourage teachers to integrate learning strategies that not only focus on literal reading skills but also foster epistemological awareness as a foundation for developing critical literacy.